Documentation and agile methods: striking a balance - Clear, Tony (ACM, 2003)
I have written previously about the need for students to develop discrimination as part of their preparation for professional practice during their undergraduate capstone courses. But nowhere is this need for discrimination more problematic than in the area of software documentation. Perhaps the only consolation is that professional developers are equally challenged. Yet in migrating students from the set of beliefs and practices that may have worked for them in programming-in-the-small, to those required for programming-in-the-large, sound documentation practices are critical to effective development and delivery of a professional product.